Farming in the Forests of Florida - Brian Becker; Sarah Workman (EDIS)
Forest settings can provide an ideal location for cultivating many valued plants which prefer shaded conditions. There are many nontimber forest products including animals and shade tolerant plants which can be intentionally promoted by specific management practices. When considering alternatives for forested land several elements need to be investigated to identify how feasible forest farming will be given the available resources, site characteristics and plans for the land. Ideal forest crops have a relatively high value and are capable of producing profitable volume over the preferred time frame. This fact sheet presents some examples of forest farming appropriate for Florida's forests. This document, CIR 1434 is one of a series through the Center for Subtropical Agroforestry (CSTAF), School of Forest Resources and Conservation, Institute of Food and Agriculture Sciences, University of Florida. First published March 2003.